Going Back to the Beginning: Aristotle and Machiavelli on Mixed Government - Lev, Amnon (Classica et Mediaevalia, 2026)
The article proposes a joint reading of Aristotle’s and Machiavelli’s conceptions of mixed government. It brings out the shared understandings of political life that inform their work and asks why they end up proposing diametrically opposed modes of government. The article relates this divergence to differences in how they view the relationship between citizens and polity. The article documents these differences in a comparison of Aristotle’s and Machiavelli’s conceptions of war and relates Machiavelli’s doctrine to developments in late medieval reflection on civil order. In conclusion, the article interrogates Machiavelli’s programmatic intention on returning political thought to its origin and concludes that his understanding of agency does not allow him to recover or reconnect to Aristotle.